Distributions of relaxation times in relaxor ferroelectric Ba(Ti0.8 Ce0.2)O3. (10th December 2019) - Adamchuk, D.; Grigalaitis, R.; Svirskas, S.; Macutkevic, J.; Palaimiene, E.; Banys, J.; Mitoseriu, L.; Canu, G.; Buscaglia, M. T.; Buscaglia, V.
Abstract: The dielectric behavior of the Ba(Ti0.8 Ce0.2 )O3 ceramics was studied by broadband dielectric spectroscopy in a temperature interval 140–500 K. The broad dielectric relaxation was analyzed by the Havriliak–Negami relationship and the distribution of relaxation times formalism. It was found that the Havriliak–Negami average relaxation time, longest and most probable relaxation times from the distribution of relaxation times follow the Vogel–Fulcher law. The freezing temperature of the longest relaxation time is substantially higher than the freezing temperature of the most probable relaxation time, indicating the distribution of freezing temperatures. The dielectric dispersion has all features inherent to relaxor ferroelectrics and the relaxation is assigned to the dynamics of polar nanoregions.